Families’ Acceptance, Concerns and Obstacles Towards COVID-19 Vaccine Among Children in Saudi Arabia: A Cross Sectional Survey: Pharmaceutical Science-Pharma - Almatrafi, Lamya Abdullah; Fagieha, Refal Essam; Simsim, Mohammed Abdulmuti; Falemban, Alaa H.; Alsanosi, Safaa M.; Bukhary, Deena; -Hindi, Yosra AL (International Journal of Life Science and Pharma Research, 2022)
While coronavirus disease 2019 has become a pandemic, the necessity of vaccination is crucial. Early 2020, scientists across the world started their vaccine trials to fight the pandemic. More than 46 million doses of a COVID-19 vaccines have been administered in Saudi Arabia. However, vaccine hesitancy, especially from parents towards their children can be an obstacle. As the parents can be hesitant, they can refuse or deny to vaccinate their children. Our aim is to investigate families’ acceptance, concerns, and obstacles related to COVID-19 vaccine among children in Saudi Arabia. Cross-sectional study was conducted from January to April 2022. An online form questionnaire composed of 15 questions was distributed electronically. Our results showed a total of 250 respondents were included in the analysis, of which 78% were female and 22% male aged between 21 to 78 years old. 88% had a university education and 40% was received 3 doses of COVID vaccine, 55.5% received two doses of vaccine, 4% received only one dose and 1% not vaccinated. 64% of parents do not support their children receiving the Corona vaccine, while 36% are supportive of it. This study revealed that many parents were hesitant to give immunity against SARS-CoV-2 to their children. Further educational programs and influence from the social media for parents and community is essential to fight this hesitancy.